Effect of residual dissolved oxygen on the corrosion behavior of low carbon steel in 0.1 M NaHCO3 solution. Issue 8 (August 2018) - Xue, Fang; Wei, Xin; Dong, Junhua; Etim, Ini-Ibehe Nabuk; Wang, Changgang; Ke, Wei
Abstract: The effect of residual dissolved oxygen (DO) on the corrosion behavior of carbon steel in 0.1 M NaHCO3 solution was investigated by electrochemical measurements, corrosion mass loss test, scanning electron microscopy (SEM) and X-ray diffraction (XRD). In the initial immersion stage, the increase of the dissolved oxygen concentration led to the change of from a reductive state of active dissolution to an oxidizing state of pseudo passivation in low carbon steel. While in the final stage, all the steels transformed into the steady state of pseudo passivation. In the anaerobic solution, the formation of α-FeOOH was attributed to the chemical oxidization of the ferrous corrosion products and the final cathodic process only included the reduction of α-FeOOH, while in the aerobic solution, it included the reduction of oxygen and α-FeOOH simultaneously. As the main corrosion products, the content of α-FeOOH was increased while that of Fe6 (OH)12 CO3 was decreased with increasing concentration of dissolved oxygen. The total corrosion mass loss of the steel was promoted with the increase of dissolved oxygen concentration.